Herniation of the tuft with outgrowth of vessels through the glomerular entrance in diabetic nephropathy damages the juxtaglomerular apparatus - Löwen, Jana; Gröne, Elisabeth; Gröne, Hermann-Josef; Kriz, Wilhelm (American journal of physiology. Renal physiology, 2019)
As shown in our previous paper (Kriz W, Löwen J, Federico G, van den Born J, Gröne E, Gröne HJ. Am J Physiol Renal Physiol 312: F1101-F1111, 2017), mesangial matrix expansion in diabetic nephropathy (DN) results for a major part from the accumulation of worn-out undegraded glomerular basement membrane material. Here, based on the reevaluation of >900 biopsies of DN, we show that this process continues with the progression of the disease finally leading to the herniation of the matrix-overloaded tuft through the glomerular entrance to the outside. This leads to severe changes in the glomerular surroundings, including a dissociation of the juxtaglomerular apparatus with displacement of the macula densa. The herniation is associated with a prominent outgrowth of glomerular vessels from the tuft. Mostly, these aberrant vessels are an abnormal type of arteriole with frequent intramural insudations of plasma. They spread into glomerular surroundings extending in intertubular and periglomerular spaces. Their formation is associated with elevated mRNA levels of vascular endothelial growth factor-A, angiopoietins 1 and 2, and the corresponding receptors. Functionally, these processes seem to compromise tubuloglomerular feedback-related functions and may be one factor why Na+-glucose cotransporter-2 inhibitors are not effective in advanced stages of DN.